A female case of pleuropulmonary blastoma type 1 whose pulmonary cystic lesion was followed since neonate - Michinobu Ohno; Toshiko Takezoe; Toshihiko Watanabe; Kazunori Tahara; Tomoro Hishiki; Akihiro Fujino; Motomi Matsuo; Masataka Higuchi; Kazuteru Kawasaki; Yoko Shioda; Motohiro Kato; Chikako Kiyotani; et al. (Elsevier, 2017)
Pleuropulmonary blastoma (PPB) is a rare malignant mesenchymal tumor. It is classified into 3 subgroups, and PPB type 1 is known to be a cystic lesion with good prognosis. Here, we report a case of PPB type 1 seen in a 1-year-old girl whose pulmonary cystic lesion had been followed-up as a congenital pulmonary airway malformation since neonate. The cyst had been diagnosed as congenital pulmonary airway malformation before surgery but the final diagnosis was type 1 PPB. The tumor had a somatic mutation in exon 25 of the DICER 1 gene whereas no germline mutation was found.